New Exact Traveling Wave Solutions of the Unstable Nonlinear Schrödinger Equations. (December 2017) - Hosseini, K.; Kumar, D.; Kaplan, M.; Bejarbaneh, E. Yazdani
Abstract: The present paper studies the unstable nonlinear Schrödinger equations, describing the time evolution of disturbances in marginally stable or unstable media. More precisely, the unstable nonlinear Schrödinger equation and its modified form are analytically solved using two efficient distinct techniques, known as the modified Kudraysov method and the sine-Gordon expansion approach. As a result, a wide range of new exact traveling wave solutions for the unstable nonlinear Schrödinger equation and its modified form are formally obtained.